The Impact and Effect of Corporate Social Responsibility on Corporate Financial Performance - Pranata, Natasha Anjanette; Sihaloho , Yolanda Maghdalena; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
CSR, short for Corporate Social Responsibility, is a concept in which companies consider the social and environmental impact of their business activities. The main principle of CSR is that companies have a responsibility to contribute positively to the society and environment around them. This includes various initiatives such as philanthropy, sustainability programs, and engagement in social issues. By implementing CSR, companies can strengthen relationships with stakeholders, enhance brand image, and create long-term positive impacts. One of the key benefits of CSR is its ability to enhance a company's reputation. By committing to responsible business practices, companies can build trust with consumers, investors, and the wider community. This can lead to long-term benefits by fostering customer loyalty, attracting investments, and reducing reputation risks. Additionally, CSR can help companies comply with increasingly stringent regulations related to environmental and social issues. The implementation of CSR can also provide internal benefits to companies. By encouraging employees to engage in social and environmental activities, companies can enhance employee satisfaction and engagement. This can have a positive impact on productivity, employee retention, and the company's image as a good place to work. Furthermore, through CSR programs, companies can expand their business networks, create collaboration opportunities, and broaden their positive impact. Despite the various benefits of implementing CSR, challenges may arise in its implementation. Companies need to manage resources wisely, measure the impact of CSR initiatives, and ensure consistency with the company's values and goals. Additionally, companies need to be transparent in reporting their CSR activities to build trust with stakeholders. By addressing these challenges, companies can optimize the benefits of CSR and create a sustainable positive impact on society and the environment.